Randomized, Controlled Trial of the Safety and Effectiveness of a Contact Force–Sensing Irrigated Catheter for Ablation of Paroxysmal Atrial Fibrillation - Vivek Y. Reddy; Srinivas R. Dukkipati; Petr Neužil; Andrea Natale; Jean-Paul Albenque; Josef Kautzner; Dipen Shah; Gregory F. Michaud; Marcus Wharton; David Harari; Srijoy Mahapatra; Hendrik Lambert; et al. (2015)
Background— Contact force (CF) is a major determinant of lesion size and transmurality and has the potential to improve efficacy of atrial fibrillation ablation. This study sought to evaluate the safety and effectiveness of a novel irrigated radiofrequency ablation catheter that measures real-time CF in the treatment of patients with paroxysmal atrial fibrillation. Methods and Results— A total of 300 patients with symptomatic, drug-refractory, paroxysmal atrial fibrillation were enrolled in a prospective, multicenter, randomized, controlled trial and randomized to radiofrequency ablation with either a novel CF-sensing catheter or a non-CF catheter (control). The primary effectiveness end point consisted of acute electrical isolation of all pulmonary veins and freedom from recurrent symptomatic atrial arrhythmia off all antiarrhythmic drugs at 12 months. The primary safety end point included device-related serious adverse events. End points were powered to show noninferiority. All pulmonary veins were isolated in both groups. Effectiveness was achieved in 67.8% and 69.4% of subjects in the CF and control arms, respectively (absolute difference, −1.6%; lower limit of 1-sided 95% confidence interval, −10.7%; P =0.0073 for noninferiority). When the CF arm was stratified into optimal CF (≥90% ablations with ≥10 g) and nonoptimal CF groups, effectiveness was achieved in 75.9% versus 58.1%, respectively ( P =0.018). The primary safety end point occurred in 1.97% and 1.40% of CF patients and control subjects, respectively (absolute difference, 0.57%; upper limit of 1-sided 95% confidence interval, 3.61%; P =0.0004 for noninferiority). Conclusions— The CF ablation catheter met the primary safety and effectiveness end points. Additionally, optimal CF was associated with improved effectiveness. Clinical Trial Registration— http://www.clinicaltrials.gov . Unique identifier: NCT01278953.